Expert Review on Games for Basic Graphic Course Via M-Learning - Ismail, Irwan Mahazir; Zainal, Masturah; Halim, Harliana (Journal of Techno-Social, 2020)
The application of mobile learning or m-learning had been applied priviously to the world including in the Western and Asian countries. In Malaysia, especially in the Faculty of Technical and Vocational Education (FPTV), the application of Information and Communication Technology (ICT) is an important aspect of teaching and learning (PnP). Therefore, a game-based Android m-learning application for the Basic graphics course has been developed. Accordingly, the gameplay and functionality of the game-based Android m-learning game for the Basic graphics course has been conducted. A set of questionnaire forms was used as an instrument was given to three experts in their respective fields to evaluate and give a view to the developed m-learning application. The results of this study can be used as an improvement to the application developed to ensure it is in good condition.